The social semiotics of tattoos skin and self - Martin, Chris William (Bloomsbury advances in semiotics, 2019)
"Why do people put indelible marks on their bodies in an era characterized by constant cultural change? How do tattoos as semiotic resources convey meaning? What goes on behind the scenes in a tattoo studio? How do people negotiate the informal career of tattoo artist? The Social Semiotics of Tattoos is a study of tattoos and tattooing at a time when the practice is more artistic, culturally relevant, and common than ever before. By discussing shifts within the practices of tattooing over the past several decades, Martin chronicles the cultural turn in which tattooists have become known as tattoo artists, the tattoo gun turns into the tattoo machine, and standardized tattoo designs are replaced by highly expressive and unique forms of communication with a language of its own. Revealing the full range of meaning-making involved in the visual, written and spoken elements of the act, this volume frames tattoos and tattooing as powerful cultural expressions, symbols, and indexes and by doing so sheds the last hints of tattooing as a deviant practice. Based on a year of full-time ethnographic study of a tattoo studio/art gallery as well as in-depth interviews with tattoo artists and enthusiasts, The Social Semiotics of Tattoos will be of interest to academic researchers of semiotics as well as tattoo industry professional and artists" ...